Assessing ecosystem health changes in UlanSuhai Lake using hierarchical analysis and entropy method - GOU Mangmang; FENG Xueyao; LI Jianru; LI Xing (Guan'gai paishui xuebao)
【Objective】UlanSuhai Lake, a critical surface water body in the Hetao Irrigation District of Inner Mongolia, plays a vital role in supporting various sectors, including agriculture, industry and local livelihoods. Its ecological health has been influenced by diverse biotic and abiotic factors that have shown significant spatial and temporal variations. This paper is to analyze its ecological health and the underling determinants over recent years. 【Method】Ecological health of the lake was analyzed using data measured from 2015 to 2019. Key indicators considered include hydrological dynamics, physical, chemical, biological traits of the lake water, as well as social and ecological services the lake provides. The evaluation was calculated using the hierarchical analysis-entropy weight comprehensive health index.【Result】Ecosystem health of the lake showed a notable improvement over the study period. From 2015 to 2016, ecosystem health of the lake was classified as poor, transitioning to moderate from 2017 to 2018, and showing a marked improvement by 2019. Furthermore, the water quality of the lake has consistently improved over the last decade, now reaching Grade V of the national water quality standards. 【Conclusion】The hierarchical analysis-entropy weight comprehensive health index method is reliable and practical for evaluating ecological health of lakes, effectively identifying temporal changes and the underlying influencing factors. These findings provide a valuable baseline for guiding protection, management, and sustainable development of UlanSuhai Lake.